RI 3306 Progress Reports - Metallurgical Division - 12. Annual Report Of The Metallurgical Division, Fiscal Year 1935 ? Introduction - R. S. Dean (The National Institute for Occupational Safety and Health (NIOSH), 1936)
The function of the Metallurgical Division is to conduct investigations relating to the treatment of mineral products from the state in which they are mined to the refined metal or other unfabricated product. These investigations include scientific and practical studies of ore dressing, covering the crushing and grinding of ores, separation by gravity, flotation. and magnetic methods; the hydrometallurgical treatment of ores, including cyanidation and amalgamation of the precious metals; the smelting and refining of copper, lead, and zinc, as well as the rare metals; and steel-melting practices from the raw ore to the finished steel. The object of this work is to conserve natural resources and eliminate waste by furnishing information on current methods of metallurgical practice. making fundamental studies of metallurgical processes, and developing new processes to the point of demonstrating their practicability. The Division is made up of sections devoted to the several phases of this work, each section being headed by an investigator capable of supervising his particular work. The work is carried on at the experiment stations and field offices or in the field, whichever seems best suited for the work in hand. The following, projects should be mentioned as particularly outstanding among those consummated successfully during the year: 1. Application of the type of chemicals known in the textile industry as wetting-out agents to flotation and agglomeration of ores, particulary soluble salts such as sodium and potassium chloride which must be treated in saturated brine. 2. Demonstration or a linear relation between surface and coercive force in magnetic minerals and Its application to magnetic separation and to the determination of grinding efficiencies and other metallurgical data which require surface determination at very fine sizes. 3. Pilot-plant demonstration of the practicability of the reduction of iron ore by natural gas and conversion of this direct iron into steel by direct melting and by forging and rolling before melting. The structure and properties of the iron so produced were studied in detail. This report covers the fiscal year July 1. 1934, to June 30, 1935.